Enhancement of microwave absorption performance of porous carbon induced by Ce (CO3) OH - Wang, Jijun; Chen, Yuhua; Wei, Yaxing; Li, Yan; Li, Fangyuan; Li, Bingzhen; Wu, Qingqing; Zhao, Jinlong (Frontiers in Chemistry, 2023)
In recent years, electromagnetic pollution has become more and more serious, resulting in a very negative impact on people's health. Therefore, it is important to develop efficient microwave absorbers to reduce electromagnetic pollution. Here, we construct a novel absorbing material of the polymer gel-derived porous carbon decorated by rare earth compounds (Ce(CO3)OH). When the thickness is 2.2 mm, the composite exhibits excellent microwave absorption performance with the optimal RLmin value and EAB reached up to -47.67 dB and 5.52 GHz , respectively, covering the ku band. The high-efficiency microwave absorption is mainly attributed to the synergistic effect of dipole polarization, defect polarization and interfacial polarization. This work not only provides a new view for designing superior absorber materials, but also lay a foundation for their real applications.